2006
DOI: 10.1158/1078-0432.ccr-06-0383
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Positron Emission Tomography Using [18F]Fluorodeoxyglucose for Monitoring Response to Chemotherapy in Metastatic Breast Cancer

Abstract: Purpose: To evaluate the clinical value of positron emission tomography (PET) for monitoring chemotherapy in metastatic breast cancer. Experimental Design: Twenty patients with hormonorefractory or hormonoreceptor-negative multimetastatic breast cancer were prospectively included. PET studies were done at baseline, at day 21 after the first cycle and at day 21 after the third cycle of chemotherapy. Metabolic response was defined based on visual and various modes of standardized uptake value (SUV) analysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 17 publications
(14 reference statements)
2
20
0
7
Order By: Relevance
“…Some studies suggested that imaging as early as after 1 cycle of chemotherapy could predict response (69), akin to the neoadjuvant therapy setting. However, other studies have not shown similar accuracy for early repeated 18 F-FDG PET (67). The level of 18 F-FDG uptake after therapy has also been shown to be predictive.…”
Section: Response To Therapy Overviewmentioning
confidence: 91%
See 1 more Smart Citation
“…Some studies suggested that imaging as early as after 1 cycle of chemotherapy could predict response (69), akin to the neoadjuvant therapy setting. However, other studies have not shown similar accuracy for early repeated 18 F-FDG PET (67). The level of 18 F-FDG uptake after therapy has also been shown to be predictive.…”
Section: Response To Therapy Overviewmentioning
confidence: 91%
“…Several relatively small studies have been conducted evaluating serial 18 F-FDG PET for measuring MBC response to treatment. Most studies showed, similar to neoadjuvant therapy, that response is accompanied by substantial drops in 18 F-FDG uptake, typically 40%250% or more from the pretherapy baselines (67)(68)(69). Some studies suggested that imaging as early as after 1 cycle of chemotherapy could predict response (69), akin to the neoadjuvant therapy setting.…”
Section: Response To Therapy Overviewmentioning
confidence: 99%
“…On pourrait ainsi modifier rapidement le traitement instauré en cas d'é volution dé favorable. Plusieurs articles ont é té publié s à ce sujet [60,74]. Il serait utile de disposer d'un examen PET-scan pré traitement.…”
Section: Mé Tastases Osseuses Hé Patiques Pulmonaires Et Ganglionnaunclassified
“…18 F-fluorodeoxyglucose positron emission tomographycomputed tomography (FDG PET/CT) has been important in the management of breast cancer patients [6]. It is used for screening for the extra-axillary lymph node metastasis [7] and distant metastasis [8,9], assessing for the treatment responses [10,11], and predicting prognosis [12], but the benefit of FDG PET/CT scanning for staging remains a matter of debate [13]. Several studies have suggested that the characteristics of FDG uptake in breast cancer are relevant to biological or histological attributes of primary tumor, including its biomarker status [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%